2023
DOI: 10.2478/sjph-2023-0013
|View full text |Cite
|
Sign up to set email alerts
|

Peer Support as Part of Scaling-Up Integrated Care in Patients with Type 2 Diabetes and Arterial Hypertension at the Primary Healthcare Level: A Study Protocol

Abstract: Introduction Type 2 diabetes (T2D) and arterial hypertension (AH) are among the greatest challenges facing health systems worldwide and require comprehensive patient-centred care. The key to successful management in chronic patients is self-management support, which was found to be only weakly implemented in Slovenia. The aim of the study is to develop an evidence-based model of peer support for people with T2D and AH at the primary healthcare level in Slovenia, which could represent a potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
(76 reference statements)
0
8
0
Order By: Relevance
“…These findings align with the results of our own study, and two possible solutions were identified. The introduction of peer supporters, who share their own experiences in managing HTN or T2D, is likely to be accepted by all participants ( 30 ). In addition, the implementation of telemonitoring can improve care for vulnerable patients, such as the elderly or those living in geographically distant areas ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings align with the results of our own study, and two possible solutions were identified. The introduction of peer supporters, who share their own experiences in managing HTN or T2D, is likely to be accepted by all participants ( 30 ). In addition, the implementation of telemonitoring can improve care for vulnerable patients, such as the elderly or those living in geographically distant areas ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Peer support also plays a positive role in hypertension control [ 64 ]. Research suggests that peer support may enhance the scope of comprehensive care, contributing to the sustainable development of healthcare systems [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Understanding and addressing factors influencing workload is crucial for developing interventions to improve efficiency, reduce work pace, and prevent burnout ( 17 , 27 ). For the sustainability of the Slovenian healthcare system it is essential to transfer health competences and responsibility from healthcare professionals to empowered patients ( 8 , 29 ). To this end, CHCL recently introduced a model of peer support with trained lay individuals who are CHCL’s volunteers and ambassadors, with the aim of empowering patients, family members and informal caregivers in the local community ( 29 ).…”
Section: Discussionmentioning
confidence: 99%